Scientific And Theoretical Aspects of Musical Thinking - Durdona Murodova (Zien Journals, 2021)
This article introduces the concept of musical thinking. The musical thinking of the great thinkers of the Middle Ages is analyzed.
Keywords: Contemplation; thinker; musical consciousness; musical feeling